2014
DOI: 10.1007/s00125-014-3313-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium–vitamin D co-supplementation on metabolic profiles in vitamin D insufficient people with type 2 diabetes: a randomised controlled clinical trial

Abstract: ClinicalTrials.gov NCT01662193 FUNDING: Clinical Research Council, Isfahan University of Medical Sciences, Isfahan, Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
77
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 42 publications
13
77
0
2
Order By: Relevance
“…The quality assessment of the studies resulted in 14 out of 23 studies having a good quality (Appendix 1, see section on Appendix given at the end of this article) (12,19,20,21,22,23,24,25,26,27,28,29,30,31). The main characteristics and main outcomes of the included studies are given in Table 1.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality assessment of the studies resulted in 14 out of 23 studies having a good quality (Appendix 1, see section on Appendix given at the end of this article) (12,19,20,21,22,23,24,25,26,27,28,29,30,31). The main characteristics and main outcomes of the included studies are given in Table 1.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…The main characteristics and main outcomes of the included studies are given in Table 1. All studies had a randomized controlled trial design, of which 18 studies used a placebo for control (12,19,20,22,23,24,25,27,29,30,31,32,33,34,35,36,37,38), three studies compared vitamin D fortified yoghurt versus plain yoghurt (21,28,39), one study used oral calcium supplementation for control (26), and one study used vitamin C supplementation for control (40). Apart from two studies, which solely included post-menopausal women (21,33), all studies included both men and women.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were similar to a parallel designed randomized placebo-controlled clinical trial, conducted by Tabesh, et al which reported reduced HbA1c levels (change from baseline of -0.70 ± 0.19%, p= 0.02) with vitamin D supplementation. 28 Another crosssectional study by Bonakdaran, et al done with 119 type 2 diabetic patients showed that calcitriol therapy resulted in significant reduction in HbA1c levels (-0.8%, p=0.01). 29 Similarly, a study was done by Hamid, et al to evaluate the effect of adding vitamin D to therapeutic regimen of type 2 diabetic patients compared to placebo.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, to estimate the nutrient intakes of the participants, we used a 3-day food diary. However, the reliability and validity of 3-day food diary for Iranian adults have been previously confirmed in vitamin D supplementation studies [48-49]; but this method may not be able to capture the habitual dietary vitamin D intake, as the individual’s day-to-day variations may be high among most of the populations. In addition, we believe that hypercalcemia is a strong indication of vitamin D toxicity.…”
Section: Discussionmentioning
confidence: 99%